In vivo fluorescence-based characterization of cytochrome P450 activity during embryonic development of zebrafish (Danio rerio) - Lörracher, Ann-Kathrin; Grethlein, Martin; Braunbeck, Thomas (Ecotoxicology and environmental safety, 2020)
Zebrafish (Danio rerio) early life-stages are increasingly gaining attention as an alternative model in both human and environmental toxicology. Whereas there is amble knowledge about the transcription of various cytochrome P450 isoforms, the level of information about functional implications is still limited. This study investigated the development of CYP2-dependent 7-methoxycoumarin-O-demethylase (MCOD) activity throughout the early zebrafish development from 5 to 118 h post-fertilization (hpf) via confocal laser scanning microscopy. Results demonstrate that zebrafish embryos exhibit constitutive MCOD activity from as early as 5.5 hpf. Characteristic spatiotemporal patterns were documented with MCOD activities localized in several tissues and organs, namely the cardiovascular system, the brain, the digestive system, and the urinary tract. The study thereby contributes to a better understanding of the development and functional role of CYP enzymes in zebrafish early life-stages.
Gesehen am 31.03.2020